(untitled) (Baghdad Science Journal, 2022)
CD63 is -one of the tetraspanin family proteins, which are regarded as: hallmark exosomal markers because it is absent from other types of vesicles. It is expressed in the cell membrane of cancer cells, and cytoplasm of stromal cells. Objective: To assess CD63 expression in gastric cancer (GC) patients, and detected if it could be used as a predictive marker. Furthermore, the current study aimed to find the correlation between CD63 expression and clinicopathological parameters as: gender, age, invasion depth, histopathological type, involvement of lymph nodes, grade and stages of GC (TNM). The current study is a retrospective study in the period time from (2018 to-2020); 50 randomly patients formalin-fixed paraffin embedded blocks (FFPE) of stomach tissue (10 cases normal tissue without GC as control, and 40 patients with GC) with its reports and diagnosis were collected from Pathology Department of the Gastroenterology and Hepatology Teaching Hospital and some private hospitals. The histological sections were stained by hematoxylin and eosin stain (H&E), and immunohistochemistry (IHC) stain for CD63. Statistical analysis accomplished by SPSS system at (P ≤ 0.05). This study indicated that there were significant differences between control group, and patients group in the expression of CD63, also there was a significant correlation between CD63 expression, and histopathological subtype, invasion depth, involvement of lymph node, and stages in patients, whereas there was a non- significant association between the age, grade, and gender of patients, and the expression of CD63.This result indicates that CD63 could be a good prospective marker in Iraqi cancer patients.